Quality management in Pakistan's export oriented industries - Fatima, Mahnaz (Oxford University Press, 2008)
This book is a study of nine industrial sub-sectors and demonstrates how industry can maintain its growth path independently of govenment incentives and protection through increased competitiveness based on quality, cost, and high responsiveness to changing customer needs and external environmental factors. It highlights the importance of quality management through scientific study